Sundanese Sufi Literature and Local Islamic Identity: A Contribution of Haji Hasan Mustapaâs Dangding - Rohmana, Jajang A. (Al-Jamiah: Journal of Islamic Studies, 2012)
In many scholarly discussions, the network of Malay-Indonesian ulama has gained important attention as it is maintained as the major element contributing to the process of Islamization in Sunda region (West Java), whereas the articulation of Islam in the lights of the indigenization efforts of Islam is often neglected. The article discusses dangding as one of Sundanese metrical verses by a renown Sundanese poet, Haji Hasan Mustapa (1852-1930). It is argued that dangding of Mustapa demonstrates a type of dialogue between sufism and Sundanese culture. Through his dangding, Mustapa successfully brought Islamic mysticism into Sundanese minds. The main focus of this study is to emphasize the significances of the position of Mustapaâs dangding in the light of network of Islamic scholars in the archipelago and of the contribution of Sundanese mystical dangding to the local literacy traditions and to the making of Sundanese-Islamic identity.[Pendekatan jaringan ulama Melayu-Indonesia selalu mendominasi banyak kajian Islamisasi di wilayah Sunda (Jawa Barat), sementara artikulasi Islam dalam artian pribumisasi Islam di wilayah tersebut kerap kali dikesampingkang. Artikel ini membahas dangding sebagai salah satu bentuk sastra Sunda, khususnya yang ditulis oleh Haji Hasan Mustapa (1852-1930). Penulis berpendapat bahwa dangding tersebut merupakan salah satu ekspresi budaya yang mengakulturasikan tasawuf dalam konteks masyarakat Sunda. Artikel ini mengulas signifikansi dangding yang dikreasi oleh Haji Hasan Mustapa dalam konteks jaringan kesarjanaan muslim di Indonesia dan kontribusi dangding dalam pembentukan identitas Islam Sunda.]